(untitled) (The Research of Medical Science Review, 2025)
The integrative review explores the synergistic therapeutic potential of bioactive compounds in Capparis decidua (Kair) and Salvadora oleoides (Peelu), two ethnobotanically significant plants from arid zones. Both species are rich in flavonoids, alkaloids, glucosinolates, and phenolic acids, demonstrating antioxidant, anti-inflammatory, antimicrobial, anticancer, and antidiabetic properties. Recent studies highlight that their combined extracts exhibit enhanced bioactivity compared to individual treatments, attributed to multi-target modulation and pharmacokinetic interactions. For instance, synergistic effects include superior free radical scavenging (DPPH: 81% vs. 74.2% and 70.5%), broader antimicrobial action (e.g., 18 mm zone against E. coli), and improved glucose reduction (47.2% vs. 36.5% and 29.7%). Mechanistic insights reveal complementary phytochemical profiles—C. decidua’s glucosinolates and S. oleoides’ isothiocyanates—targeting oxidative stress, inflammation, and metabolic pathways. Despite promising preclinical data, clinical validation, standardization, and long-term safety studies remain critical for translating these findings into polyherbal formulations. The review underscores the plants’ potential as cost-effective, multi-target therapies for chronic diseases while advocating for advanced research in omics-guided drug development and regulatory harmonization.